Psychoanalysis of the Character's Anxiety Emotion in Script Inside Out 2 Movie - Taufan, Azhar Shakti; Tawami, Tatan (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2024)
This research is titled